Willingness to pay for improved solid waste collection services in a commercial center in Sango, Nigeria - Francisco, Onukogu Humpherey (2018)
Solid waste is a serious environmental problem in both developed and developing countries. Improper management of solid waste has been reported by several researchers in different cities of developing countries. In Nigeria, cities being among the fast growing in the world are faced with the problem of solid waste management. Of the different categories of wastes being generated, solid waste from commercial areas had posed a hydra-headed problem beyond the scope of various solid waste management systems in Nigeria. The objective of this study is to estimate the respondents’ willingness to pay for improved solid waste collection services in commercial center of Sango, Nigeria. The study employed dichotomous choice contingent valuation and choice experiment in commercial area of Sango using faceto- face questionnaire interview on 200 vendors who were selected using in simple random sampling method. From the result of a binary logistic regression model obtained, it shows that the mean willingness to pay amount was N1490.54 approximate ly, N1500 per business unit monthly. This figure indicates that the respondents were willing to pay higher amount than the currently charged amount (N1000), which revealed the existence of consumer surplus. The result from the choice experiment shows that the respondents place higher preference for the improvement on frequency of collection (scheduled 4-times per month). The second most preferred attribute was the number of users per dustbin, where they preferred individual user per dust bin. However, the dustbin type was the least preferred attributes by the respondents, where it carries the least coefficient value from the model. The results of this study would enrich our understanding of willingness to pay for waste collection services in commercial areas in Nigeria and provide a guide to policy makers. This study recommend that policy makers can choose from a set of scenarios, which includes different levels of attributes and WTP estimates for each attribute, in designing an improved solid waste management project for Sango. Also, there is the need for upward review of the currently charged solid waste management fee of N1,000 to N1,500 to eliminate consumer surplus, as the respondent revealed their willingness to pay the amount.